Văn hóa doanh nghiệp, sự hài lòng và cam kết gắn bó của nhân viên với tổ chức trong các doanh nghiệp kinh doanh sản phẩm điện tử tại TP. Hồ Chí Minh - Trịnh Thùy, Anh; Phan Tường, Vi (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2017)
This article analyzes the effects of different constructs of corporate culture on employee satisfaction and organizational commitment. 200 interview responses collected from managers and employees working in HCMC-based electronic trading enterprises are used for exploratory factor, correlation, and regression analyses. The results indicate that the five factors of corporate culture comprise training and development, rewards and recognition, working environment, policies, and future orientations, which are found to have positive effects on employee satisfaction and thus on organizational commitment. Several implications are accordingly proposed with a focus on bettering corporate culture and promoting organizational commitment.
Keywords: Cam kết gắn bó; Employee satisfaction; Organizational commitment